Analisis Kecemasan Dengan Kepuasan Pasien Tentang Pelayanan Keperawatan Rumah Sakit Wilayah Majalaya - Situmorang, Roganda; Mukaroma, Raihany Sholihatul; Nugraha, Dedep; Pritama, Julham (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2024)
Nursing services are a service that has a big impact on hospital services, so it requires a high level of patient satisfaction to maintain and improve hospital services. Based on a study of the situation of the Nursing Management Profession at one of the hospitals in the Majalaya region in 2023, the patient satisfaction rate for nursing services was 78%, still far from the expected target of 95%. The situation study informed that patients experienced anxiety in facing the process of health problems, including 70% experiencing feelings of fear, 78% experiencing tension, 75% experiencing worry and 79% experiencing emotional changes. The aim of this research is to analyze the relationship between anxiety and patient satisfaction regarding nursing services at one of the hospitals in the Majalaya region. The research uses a quantitative research method, descriptive correlation design, cross sectional approach. The sampling technique used incidental sampling of 70 respondents. Data collection used primary data by distributing an anxiety questionnaire (SRAS) with a Cronbach Alpha value of 0.964 and a modified Kotler and Armstrong (2016) patient satisfaction questionnaire with a Cronbach Alpha value of 0.977. The results showed that 61.4% of patients' anxiety was mild, 18.6% moderate, and 20% severe. The research results also showed that patient satisfaction was 20% low, 60% sufficient, and 20% high. The results of the p-value analysis in this study were 0.000, which shows that there is a relationship (of 81%) between anxiety and patient satisfaction regarding nursing services at one of the hospitals in the Majalaya region. The lower the level of patient anxiety, the higher the level of patient satisfaction regarding nursing services. Efforts are needed to identify and handle patient anxiety (through educating the patient's needs and relaxing) during the process of nursing services in order to obtain patient satisfaction.Keywords : Anxiety, Nursing, Patient, Satisfaction, Service